Keragaman Genetik dan Heritabilitas Berbagai Karakter Tanaman Kedelai (Glycine max (L.) Merril) - Deviona, Deviona; Roslim, Dewi Indriyani; Zul, Delita; Suhartina, Suhartina; Syafitri, Artica Ria (Agrosains : Jurnal Penelitian Agronomi, 2024)
The purpose of this study was to determine the genetic diversity and heritability values of the morphological characters of several genotypes of soybean plants. The study used a completely randomized design (CRD) consisting of fourteen genotypes and three replications. The observed parameters were flowering age, harvesting age, plant height, number of nodes, crown width, stem diameter, number of fruitful pods per plant, total number of pods per plant, total number of seeds per plant, number of fruitful seeds per plant, number of seeds per pods, 100 seed weight, and seed weight per plant. Data were analyzed by analysis of variance using SAS version 9.0, followed by Duncan's multiple range test (DNMRT) at the 5% level. The results showed that the characters were flowering age, harvesting age, plant height, number of nodes, stem diameter, total number of pods per plant, number of seed pods per plant, total number of seeds per plant, number of seeds per plant, number of seeds per pod, weight seed per plant, has a wide genetic diversity. Crown width characteristics have narrow genetic diversity. All characters showed wide phenotypic diversity. The heritability results showed that the characteristics were flowering age, harvesting age, plant height, number of nodes, crown width, stem diameter, total number of pods per plant, number of seed pods per plant, total number of seeds per plant, number of seeds per plant, and number of seeds per plant. Pods and seed weight per plant were classified as having a high heritability. The characteristics of flowering age, harvesting age, plant height, number of nodes, stem diameter, total number of pods per plant, number of fruitful pods per plant, total number of seeds per plant, number of fruitful seeds per plant, number of seeds per pod, and seed weight per plant can be used as selection criteria because they have a wide genetic diversity and high heritability value.